Root Distribution Pattern of Three Chili Varieties on Vertisol Soil, Central Lombok - Zuhdiyah Matienatul Iemaaniah; Mahrup Mahrup; Lolita Endang Susilowati (Pascasarjana, Mataram University, 2023)
Plant roots have an important role in plant growth. Roots function as absorbers of water and other nutrients in the soil which are distributed to other body organs. Distribution patterns, root growth and root range influence plant growth and development. Vertisols are one of the dominant soil orders in southern Lombok, but their physical characteristics are rich in monmorillonite type clay which expands when wet and shrinks when dry. This study aims to analyze the pattern of root distribution through the root growth rate of the three chili varieties and to analyze the tolerance level of the three chili varieties. The field experiment was organized according to a Randomized Completely Block Design with three replications. The varieties of chili plants planted are Kara chilies, Dewata chilies and local chilies. Root growth rate was measured on serial plant samples observed every 20-day interval until day 60, during the growth period. The results obtained showed that the distribution patterns of the three varieties experienced an increasing trend in the rate of root growth, for the kara varieties it reached a figure of 4.65 cm, for local varieties is 5.54 cm; and in the dewata variety it is 2.67 cm. The tolerance level of chili plants to congested conditions was seen from the results of their root growth rates, the three varieties showed that they were Semi Tolerant (ST) to waterlogged environmental conditions on vertisol soils.